ETHICAL AND LEGAL IMPLICATIONS OF GENE EDITING - Duardo Sánchez, Aliuska (2020)
The aim of this paper is to address, from the areas of Ethics and Law, the scope of one of the biotechnologies that is generating most impact in the doctrine due to its potential clinical application. This is due to the infinite possibilities promised by gene editing, and more specifically, its famous tool: CRISPR/Cas9. Among its possible applications are the repair of serious diseases in human germinal cells, preventing their eventual transmission to descendants. However, it could, as one of the many works coordinated and co-written by our mentor, Professor Romeo Casabona, rightly calls it, go "beyond health", giving rise to eugenic reminiscences, which would be represented by human enhancement. Consequently, we will analyse, on the one hand, the ethical acceptability of gene therapy in the face of improvement, in consideration of the bioethical principles of autonomy, beneficence, non-maleficence and justice. On the other, will think in the effect that gene editing indiscriminate use could have on fundamental rights, especially in terms of human dignity, equality and identity, as well as on the unaltered genetic heritage and the responsibilities towards future generations, which Professor Romeo has been a pioneer in envisaging.